Robustness analysis and control of uncertain descriptor systems - Chong, Lin. (2008)
This thesis presents some work on the analysis and control for uncertain descriptor systems. The analysis part includes robust stability, robust closed-loop stability, and robust controllability and observability. We first deal with the stability ro-bustness of uncertain descriptor systems and derive a norm bound for uncertain descriptor systems to be regular, impulse-free and stable. The problem of the so-called robust impulse controller of the uncertain system is also considered. Then, we study a class of uncertain linear descriptor systems with interval plants, and give a necessary and sufficient condition for the so-called robust structural stabil-ity. Next, we consider the robust stability of closed-loop systems with structured perturbations under preconstructed static output feedback, and give necessary and sufficient conditions. Using the presented method, necessary and sufficient condi-tions for robust open loop stability are also established.